Selling State Assets: Three Options - TOL, RICHARD; GORECKI, PAUL (ESRI, 2011)
Under the EU/IMF Programme for Financial Support for Ireland, the government undertook to consider the potential for disposing of State assets. In the 2011 Programme for Government a target of up to ?2 billion was set for the sale of non?strategic State assets, but only after adequate regulatory structures to protect consumers were in place. The State owns important parts of the economy ? including the ports, airports, electricity generators, and transmission systems (gas and electricity). It also owns a household waste collector, a tour operator, a horticulture business, and a stud farm. The sale of State assets is nothing new ? ?8.3 billion has already been raised through the sale of State assets in steel, sugar refining, banks, telecommunication and airlines. Largely as a result, the share of the commercial state sector in total employment fell from 8 per cent of total employment in 1980 to 2 per cent in 2008.
PUBLISHED
Keywords: Economics; Ireland; State asset disposal